The Impact of Health Education on Knowledge of Kidney Function and Health on Children at Yayasan Generasi Muslim Cendekia - Saraswati, Putu Bella Aprillia; Nurhidayati, Siti Zainiah; Hikmaturrohmi; Maulana, Farreh Alan; Handayani, Ervina; Ramadhan, Moch. Fitrah; Tate, Kazuma; Shinozuka, Miho; Ikunaga, Arisa; Miyake, Masao; Hazama, Akihiro; Prasedya, Eka Sunarwidhi (Postgraduate, University of Mataram, 2024)
The kidney is the main organ of the excretory system that performs a very vital function in the human body. Chronic Kidney Disease (CKD) is a disease that greatly affects human quality of life, especially children. The disease can be prevented with basic knowledge about kidneys, their functions, and how to maintain kidney health. This study aims to determine the effect of providing education on knowledge of kidney function and health integrated with educational materials and a simple educational board game of kidney function on students' knowledge. The research method used the quasi-experimental technique with one group pre-test and post-test design. Data analysis used an N-gain test to determine the improvement of students' critical thinking skills and a t-test to determine the effect of educational materials and a simple educational board game of kidney function on students' knowledge. The data was collected using a pretest-posttest involving 30 teenage students. The t-test results indicate a significant difference between pretest and posttest critical thinking skills (p < 0,05). A high category N-gain score of 0,972 was achieved. This study concludes that educational materials and a simple board game of kidney function effectively enhance student's knowledge